Four steps to ensuring best practice in new brand launches - Crisafulli, Benedetta; Singh, Jaywant (Ntc Publications, 2017)
When introducing new brands and/or extensions, substantial promotion is often used to encourage trial and purchases. But are marketing communications at new brand launch effective? What are the best practice tools for measuring the success of new brands and extensions?
Best Practice: Optimising New Brand Launches
The publication concerned actively disallows open access.